One Real-time Micro-thrust Measurement System Based on Barkhausen Effect. (August 2019) - Du, Xinru; Wu, Jianjun; Ou, Yang; Li, Jian; Wu, Biqi
Abstract: The thrust of the electric thruster for micro-nano satellites is very small, so it is very difficult to accurately measure the real-time variation of micro-thrust. In order to solve this problem, a real-time micro-thrust measurement system based on Barkhausen effect is proposed. Buckhausen effect is that under the action of external stress, the change of internal stress or strain of ferromagnetic material will cause the change of permeability, reluctance and flux of ferromagnetic material, which will result in Barkhausen noise under the external alternating magnetic field. Therefore, the change of stress or strain in ferromagnetic materials can be obtained by measuring Barkhausen noise. The micro-thrust measurement system based on Barkhausen effect proposed exactly in this paper transforms the change of thrust into the change of internal stress of the magnetoelastic element [1], which can realize real-time and high-precision measurement of instantaneous micro-thrust with the advantages of simple structure, easy operation and high reliability.